Spatial aggregation of indicators in sustainability assessments: Descriptive and normative claims. (July 2018) - Allain, S.; Plumecocq, G.; Leenhardt, D.
Highlights: Indicators are viewed as objects to describe and debate a situation. Indicators result from different information processes that are sometimes "hidden". The process of spatial aggregation is investigated. Spatial aggregation choices provide a degree of leeway in interpreting indicators. Choices illustrate tension between the need for consistency and that for diversity. Abstract: Indicators are widely used in sustainability assessments. They serve both a descriptive function (i.e., assessing a situation or effects of potential changes) and a normative function (i.e., allowing the expression of value judgments). These functions are usually considered when identifying and using indicators. However, processes such as formalization, estimation, and customization are needed to produce tangible indicators. These processes and their influence on sustainability assessments are studied less often. We focus on spatial aggregation, a specific type of customization commonly used for landscape-scale and regional assessments. Using a database with 146 indicator profiles for water management, we investigated reasons for spatial aggregation choices, i.e. whether indicators based on spatially-explicit data are aggregated while under development or are provided to users in a disaggregated form. Although the literature assigns a descriptive function to spatial aggregation, our database shows that reasons underlying aggregation choices are more diverse. These reasons include highlighting differences, fitting to the scale of a process, fitting to criteria, recognizing a lack of knowledge, expressing social rationality, contextualizing information, and allowing different interpretations of the same indicator. Some of these reasons reflect the choice to expand or reduce the range of potential uses of an indicator, and therefore the potential for different viewpoints to confront each other. Hence, normative claims combine with descriptive claims when aggregating indicators, and even more so when customizing them. In general, the form of indicators merits more attention in the practice and theory of sustainability assessments.